Per una revisione del concetto di nevrosi: dal sintomo manifesto alla manifestazione dell’assenza - Vari, Autori (Il sogno della farfalla, 2006)
The authors highlight how a number of pathologies, originally considered neuroses but now seen as anxiety disorders in the current nosographic classifications of the DSM IV, hide much more serious psychopathologies even though they may not be directly manifest. Such an elaboration, resulting from the experience of the Collective Analysis and from the development of M. Fagioli’s theory on mental illness which the authors of this article refer to in their daily clinical work, restores some notions of classical psychopathology which have been lost over time but would seem to appear crucial for the diagnosis: such as concepts of ambulatory schizophrenia (Zilboorg), latent psychosis (Bleuler), psychopathic fact (Minkowski). It can also be argued that the substantial indifference to the symptom, present in some patients, forms an alliance with a culture that tends to aim for the maximum result with the minimum effort and tends to minimize psychiatric research into the causes. In this way the psychiatrist fails to fulfil his/her duty as a doctor and risks appearing ever more similar to the poor Chaplin of Modern times. Indifference to the symptom, the absence of affects in some presumed forms of neuroses, can only be contrasted with the presence of the psychiatrist who, by taking on the specific research into human mental reality, should tend more and more to see and frustrate those latent psychopathologies, and in so doing, denounce the superficiality of the common and reductive way mental illness is viewed.